Kolintang Minahasa: from Cultural Heritage to A Global Instrument in Inclusive Music Education and Cultural Diplomacy - Hartono, Markus Soegiarto; Cahya Septiyaningsih, Imada; Aditia, Dimas; Widyaatmadja, Swanny Trikajanti; Setiawan, Risky; Sinaga, Risma Margaretha (Universitas Negeri Semarang, 2025)
Kolintang, a wooden percussion instrument from Minahasa, North Sulawesi, has evolved from a sacred ritual object into UNESCO-recognized intangible cultural heritage in 2024. Despite this recognition, scholarship has not sufficiently examined how this transformation reshapes educational practice or how the instrument’s physical properties support inclusive music learning. This study examines Kolintang’s trajectory through an analytic autoethnographic approach grounded in five decades of direct practice within the pedagogical lineage of Petrus Kaseke, triangulated with interviews of fifteen key figures, including descendants of innovators Nelwan Katuuk and Petrus Kaseke, and empirical data from a 2024 training program for Deaf participants in Jakarta. The research documents Kolintang’s technical development from pentatonic to chromatic tuning, enabling engagement with global repertoires, and traces how diaspora communities in Java systematized ensemble-based pedagogy. Empirical findings show that ten Deaf participants achieved a mean rhythmic accuracy of 92.3 percent with a standard deviation of 5.8 percent through vibrotactile rather than auditory learning. The findings indicate that Kolintang’s sustainability depends not on static preservation but on cultural transmutation, defined as the strategic adaptation of material form to preserve philosophical and symbolic essence. Kolintang continues to function as a marker of diaspora identity, an instrument of Indonesian cultural diplomacy, and a culturally grounded medium for inclusive music education. This trajectory offers a model for sustaining intangible heritage in the twenty-first century by repositioning traditional arts as adaptive educational resources responsive to contemporary human needs.